2023
DOI: 10.1039/d2tb02416k
|View full text |Cite|
|
Sign up to set email alerts
|

LHRH conjugated gold nanoparticles assisted efficient ovarian cancer targeting evaluated via spectral photon-counting CT imaging: a proof-of-concept research

Abstract: Emerging multifunctional nanoparticulate formulations take advantage of nano-meter scale size and surface chemistry to work as a therapeutic delivery agent and a diagnostic tool for non-invasive real-time monitoring using imaging...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…In this context, a study described higher uptake of 18 and 80 nm ''as prepared'' AuNPs in ovarian cancer cells (OVCAR5 and SKOV3), and selective targeting of ovarian cancer in an in vivo model using LHRH peptide-conjugated (PEG-peptide mixed monolayer) AuNPs. 66,67 Another study also showed the accumulation of 15 nm AuNPs at the periphery of Lewis lung carcinoma implanted in mice. These studies highlight the importance of SPCCT for the detection and quantification of AuNPs in cancerous cells and tissues both in vitro and in vivo.…”
Section: Gold (79) Nanoparticlesmentioning
confidence: 97%
“…In this context, a study described higher uptake of 18 and 80 nm ''as prepared'' AuNPs in ovarian cancer cells (OVCAR5 and SKOV3), and selective targeting of ovarian cancer in an in vivo model using LHRH peptide-conjugated (PEG-peptide mixed monolayer) AuNPs. 66,67 Another study also showed the accumulation of 15 nm AuNPs at the periphery of Lewis lung carcinoma implanted in mice. These studies highlight the importance of SPCCT for the detection and quantification of AuNPs in cancerous cells and tissues both in vitro and in vivo.…”
Section: Gold (79) Nanoparticlesmentioning
confidence: 97%
“…In the context of ovarian cancer diagnosis, gold nanoformulations could be used not only as a selective drug delivery agent but also as a diagnostic tool for imaging technologies, promoting non-invasive and real-time monitoring. For instance, a recent work tested GnRH-conjugated gold nanoparticles in a mouse model of ovarian cancer to assess their use in multi-energy spectral photon-counting computed tomography ( 116 ). The authors evidenced a preferential uptake of GnRH-gold nanoparticles in organs of the abdominal cavity, suggesting that this technology has potential use for imaging of ovarian cancer.…”
Section: Gnrh-based Nano-formulations In Prostatic and Ovarian Cancermentioning
confidence: 99%
“…However, their cellular targeting levels are limited, which limits the toxic effects of drugs (68). LHRH peptidemediated multifunctional nanomaterials targeting tumors could significantly improve drug delivery and therapeutic efficacy against drug-resistant cancers (69). Pan and colleagues (53) found in a paclitaxel-resistant ST30 cell model that LHRH peptide targeting prolonged drug circulation and enhanced cytotoxicity compared to untargeted nano-delivery vehicles (IC50:3160nM vs 1285nM).…”
Section: Targeted Lhrh Peptide Receptor Therapymentioning
confidence: 99%